Bioactive compounds recovery optimization from vine pruning residues using conventional heating and microwave-assisted extraction methods - Jesus, Meirielly Santos (2019)
Polyphenol compounds from vine pruning residue (VPR) were extracted by conventional heating and microwave-assisted treatments. For each treatment, total phenolic compounds and their antioxidant activity were optimized by experimental design. Maximal extraction of polyphenolic compounds (2.17g/100g VPR) was obtained at 80°C, 120min and 45% of ethanol by conventional heating, and 2.37g/100g of VPR were extracted by microwave-assisted process at 120°C, 5min and 60% of ethanol. Ellagic acid and apigenin were the predominant polyphenolic compounds in the extracts, achieving concentration of 68.65 and 208.23mg/100g VPR, respectively for conventional heating and 185.15 and 118.84mg/100g of VPR for microwave-assisted treatment. The results showed reduction of extraction time and energy consumption for microwave-assisted treatment leading to cost-effective technology for the extraction of polyphenol compounds. Furthermore, the results hereby compiled allow for the tailor-made extraction of specific high-value compounds from a renewable biomass as vine pruning residue.